2014
DOI: 10.3182/20140824-6-za-1003.01918
|View full text |Cite
|
Sign up to set email alerts
|

A Transient Diesel EMS Strategy for Online Implementation

Abstract: A recently developed strategy for diesel engine management systems is modified to reduce the implementation complexity. The strategy calculates set points for engine management system controllable quantities with an aim to minimize fuel consumption for a given engine speed and requested torque profile, while keeping accumulated emissions below given limits. The strategy is based on the methodology for steady-state engine operation, but extended to handle transient effects in the engine caused by dynamics in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The calculation of the set points using the transient extension is more complex, and two-, three-, and four-dimensional grid maps are needed for online implementation for boost pressure set points, oxygen fraction set points, and injection timing respectively. In a recent study presented in Grahn, Johansson, and McKelvey (2014a), it is demonstrated that the strategy can be modified such that it can be implemented using only twodimensional grid maps, without significantly decreasing the performance.…”
Section: Cyclementioning
confidence: 99%
“…The calculation of the set points using the transient extension is more complex, and two-, three-, and four-dimensional grid maps are needed for online implementation for boost pressure set points, oxygen fraction set points, and injection timing respectively. In a recent study presented in Grahn, Johansson, and McKelvey (2014a), it is demonstrated that the strategy can be modified such that it can be implemented using only twodimensional grid maps, without significantly decreasing the performance.…”
Section: Cyclementioning
confidence: 99%